Audit Sistem Informasi Pendaftaran Dan Pembayaran Akhir Online Menggunakan Pengujian Black Box Dengan Equivalence Splitting Dan Analisis Marginal - Aini Salsabila; Muhamad Hasbi Hasidiqi; Fatiah Amelia; Aries Saifudin (CV. Multi Kreasi Media, 2022)
Increase the visibility (capacity) of the software as part of the system costs and facilitate better planning as a result of software failures. H. Rigorous testing. Problems often arise during development, especially during testing. Black-box testing techniques focus on the information domain of the software, partition the input domain of the program to execute test cases and provide comprehensive test coverage. Black Box itself has several test methods. In particular, graph-based testing methods examine the relationships and behavior between program objects. One of the stages of software development that must be passed is testing. The program test must first be carried out by the programmers themselves and then submitted and tested by the program testers